Geochemical investigations of early-diagenetic calcareous concretions from the Cretaceous Paja Formation (Colombia): understanding the depositional environment (2022)
In order to understand the geochemistry behind the depositional conditions and postdepositional processes of the Cretaceous Paja Formation sediments, it was necessary to measure the major elements and trace elements. This was done in order to analyze Fe/Al ratios in early-diagenetic concretions whose high content of Fe indicate a reducing (anoxic) depositional environment. Detrital input was also calculated through major elements, where a small percentage of detrital input was found in contrast of the black shales from the northern part of the Formation and the upper continental crust, suggesting that the samples analyzed in this project might be the deepest known located samples of the Paja Formation. Trace elements were useful for the calculation of redox proxies (Ni, Mo, Zn, V), which enrichment of trace elements in comparison to average shale, post-Archean average Australian shale and upper continental crust and their correlation with total organic carbon (TOC) also support an euxinic environment. In the same way, by the use of in-situ analyses, it could be determined presence of cubic and framboidal pyrite, in which the last one need specific conditions of formation where a high sulfur content is necessary. Considering the fact that TOC:TS ratios correspond to an oxic environment and not anoxic as expected, it is suggested that those concentrations could have been altered by processes like oxidation of late-diagenetic organic matter, this is supported by the majority of pyrite being oxidized, lowering its total sulfur concentrations and leaving a beehive texture on the remaining goethite and presence of minerals like gypsum that could originate from pyrite oxidation. In addition, there is the presence of late-diagenetic organic matter only in the sediments within the concretions, that confirms the idea of the concretions being the only reliable early-diagenetic samples preserved.